Customers and investors: A framework for understanding the evolution of financial institutions - Merton, Robert C.; Thakor, Richard T. (Journal of Financial Intermediation, 2019)
Financial institutions are financed by both investors and customers. Investors expect an appropriate risk-adjusted return for providing financing and risk bearing. Customers, in contrast, provide financing in exchange for specific services, and want the service fulfillment to be free of the intermediary's credit risk. We develop a framework that defines the roles of customers and investors in intermediaries, and use it to build an economic theory that has the following main findings. First, with positive net social surplus in the intermediary-customer relationship, the efficient (first best) contract completely insulates the customer from the intermediary's credit risk, thereby exposing the customer only to the risk inherent in the contract terms. Second, when intermediaries face financing frictions, the second-best contract may expose the customer to some intermediary credit risk, generating “customer contract fulfillment” costs. Third, the efficiency loss associated with these costs in the second best rationalizes government guarantees like deposit insurance even when there is no threat of bank runs. We further discuss the implications of this customer-investor nexus for numerous issues related to the design of contracts between financial intermediaries and their customers, the sharing of risks between them, ex ante efficient institutional design, regulatory practices, and the evolving boundaries between banks and financial markets.